HF-AQM: An efficient active queue management scheme for wireless local area network environment - Hassan, Suhaidi; Hassan, Atheer F.; Arif, Suki (2017)
An Active Queue Management (AQM) is a proactive scheme that controls the network congestion by avoiding the congestion before it happened.When implementing AQM in wireless networks several contemporary issues must be considered, such as interference, collisions, multipath-fading, propagation distance, shadowing effects and route failure, and whether the wireless networks is WLAN or other type.Therefore, the needs for AQM algorithm that can perform in WLAN network as good and efficient as in wired network become so crucial.This paper proposes a new AQM algorithm called Hybrid Fair AQM (HF-AQM) that can achieve better fairness and higher utilization in WLAN environment by hybridizing queue delay and input rate to measure network congestion. The simulation results show that HF-AQM manages to gain a higher fairness level in comparison to several types of AQM schemes with higher link utilization due to the adaptation and hybridization that been used in its congestion indicator, control function and feedback function.